Impact of BMI on Knee Osteoarthritis WOMAC Severity in Adults: A Cross-Sectional Study - Rajanagara, Arya Satya; Amru, Basra Ahmad; Putra, Aditya; Djajawiguna, Hafidz Naeriansyah; Iqra, Mohammad Alief; Shafira, Syifa; Putra, ⁠I Putu Wirasatya Eka; Mangun, Dhea JRN (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Background: Knee osteoarthritis (OA) is a degenerative joint disease that most often causes pain and disability in adults and the elderly. Risk factors for OA progression include age, gender, physical activity, and body mass index (BMI). Increased BMI is known to contribute to increased mechanical load on the knee joint and trigger inflammation, which can exacerbate OA severity. Objective: To assess the relationship between body mass index (BMI) and the severity of knee osteoarthritis in adult patients. Methods: This is a cross-sectional analytical study conducted at Rheumatology Clinic of Dr. Soetomo General Hospital, Surabaya, in 2019. A total of 42 patients diagnosed with knee OA who met the inclusion and exclusion criteria were enrolled. OA severity was assessed using the WOMAC (Western Ontario and McMaster Universities Osteoarthritis Index) score, while BMI was calculated based on WHO standards and categorized into normal and high (overweight/obese). Analysis of the relationship between BMI and the severity of OA was carried out using the Fisher's Exact Test, with a p value < 0.05 considered significant. Results: Most patients with normal BMI had moderate-severe OA (77.8%), while patients with high BMI were more likely to have very severe OA (58.3%). Fisher's Exact Test showed a significant association between BMI and OA severity (p = 0.0285). Patients with high BMI were more likely to have very severe OA compared to patients with normal BMI (OR ? 4.9; 95% CI ? 1.1–21.5). Conclusion: There was a significant association between increasing BMI and the severity of knee osteoarthritis. These findings emphasize the importance of weight control as part of the prevention and management strategy for knee OA in adult patients.